A hypovirulence-associated capsidless bi-segmented ssRNA mycovirus enhances melanin and microsclerotial production in a vascular phytopathogenic fungus. - Jiamin Gao; Xuekun Zhang; Jichun Jia; Huang Huang; Jiasen Cheng; Yanping Fu; Xueqiong Xiao; Bo Li; Tao Chen; Xiao Yu; Longfu Zhu; Tom Hsiang; et al. (PLoS Pathogens)
Mycoviruses are increasingly recognized for their multifaceted roles in fungal ecology, because of advances in understanding of their biology and molecular features. In this research, we identified and characterized two capsidless, bi-segmented positive-sense RNA mycoviruses: Verticillium dahliae ormycovirus 1 (VdOMV1) and VdOMV2, both of which infect Verticillium dahliae, a fungal pathogen causing vascular wilt of cotton. Phylogenetic analysis revealed that VdOMV1 and VdOMV2 cluster within the ormycovirus group, an evolutionary lineage unique to Riboviria. VdOMV2 may significantly enhanced V. dahliae melanin production and microsclerotial formation through regulating melanin synthesis-associated genes. This mediated the conversion from production of hyphae to microsclerotia, and enhanced V. dahliae survival under adverse abiotic stress conditions. Furthermore, VdOMV2 boosted the penetration ability of hyphae through cellophane membranes, while inhibiting the proliferation of V. dahliae hyphae within plants, and negatively modulated genes related to pathogenicity, possibly conferring hypovirulence. Enhancements in penetration and survival not only increase the efficacy of hypovirulent strains in overcoming environmental challenges, but also highlight the potential of VdOMV2-infected strains for managing Verticillium wilt in agricultural settings, thus representing an alternative mycovirus-based biocontrol approach for vascular fungal diseases.